PENGARUH MEDIA VIDEO ANIMASI TERHADAP MINAT BELAJAR SISWA KELAS IV SDN 1 BOJONGNEGARA - Shefira Nazma Laura; Siti Sahronih (Institut Pendidikan dan Bahasa Invada, 2022)
The low interest in learning of students and the lack of availability of class IV facilities and infrastructure at SDN 1 Bojongnegara became the motivation to carry out this research. The purpose of this study was to see how the influence of animated video media on the learning interests of grade IV students of SDN 1 Bojongnegara. This research uses quantitative methods through questionnaires as a method of collecting data. Researchers took samples from grade IV of SDN 1 Bojongnegara with a total of 30 students. A simple linear regression test is an analytical technique in this study. The objects in this study are animated video media (X) and the interest in learning grade IV students of SDN 1 Bojongnegara (Y). The results showed that the sig value < 0.05 which can be interpreted as animated video media affects the learning interest of grade IV students of SDN 1 Bojongnegara. In addition, the results of the study also showed an R value of 0.550 and an R square of 0.302, which means that animated video media affects the learning interest of grade IV students of SDN 1 Bojongnegara by 30.2%. While other influencing factors were 69.8%. Thus, it can be concluded that applying animated video media can affect the learning interest of grade IV students at SDN 1 Bojongnegara.